(untitled) (Global Journal of Science Frontier Research, 2019)
The whole material world is a material body and a torus (NEMF). This explains why the torus in the nonequilibrium theory is the tridimensional attractor to which the NEMF of the whole material world (alive and not alive) adhere. Torus (as well as all stars), our Earth, man, plants, etc. For this reason, nonlinear mathematical model was used in torus representation, in which the equations have simplest form, a presentation. This geometrical presentation shows clearly that only external perturbation can elongate the circular orbits of the planets into ellipses. Since in the search of other inhabited planets it was found that all planetary orbits in our galaxy were ellipses, the disturber must be of galactic origin. Astronomical observations found that an intruder galaxy, which our galaxy swallowed long time ago, still orbits (the Black Hole weighing millions of solar masses and the leftove This disturbs all the stars and planets in the galaxy. 2/ This makes the axis of spinning of all the stars in the galaxy, including our Sun, to wobble (called cycle of precession) in synchrony with the orbiting intruder galaxy around the center of our galaxy.